METHODOLOGICAL SUPPORT OF TRAINING STUDENTS IN A DIGITAL EDUCATIONAL ENVIRONMENT IN PEDAGOGICAL PROCESSES ON THE BASIS OF A HIERARCHICAL APPROACH - Ergashev Nuriddin Gayratovich (American Journals, 2025)
This article presents the methodological support for the training of students in pedagogical processes on the basis of a hierarchical approach in a digital educational environment. It is also said that digitization of education is an important factor in teaching, increasing students ' interest in teaching and access to information, and the introduction of educational digitization systems is considered the main stage in the introduction of modern educational environments in higher education. In addition, it is theoretically justified that the introduction of automation and digitization systems in an informed society is a prerequisite for the implementation of effective and high-quality work in various sectors of the economy, and such a need is a prerequisite for the introduction of digital technologies into the higher education system.
Keywords: Pedagogical process, digital technology, technical systems, hierarchical approach, teaching, scientific and methodological system, model, etc.